1990
DOI: 10.2190/adly-1uu0-1a8l-hpxy
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism: A Review of Neuropsychiatric Aspects

Abstract: The authors review current information about the prevalence, causes, course, and consequences of subclinical hypothyroidism. There is evidence that subclinical hypothyroidism may be associated with cognitive dysfunction, mood disturbance, and diminished response to standard psychiatric treatments. Recommendations are presented for the screening, evaluation and treatment of patients in whom subclinical hypothyroidism may be contributing to neuropsychiatric dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 54 publications
2
52
0
5
Order By: Relevance
“…44 A recent study showed no association with anxiety, depression, or cognitive dysfunction. 25 Nonetheless, it is still reasonable to have a low threshold for therapy for SCH in patients with depression, bipolar disorder, and cognitive dysfunction.…”
Section: Psychiatric and Cognitive Dysfunctionmentioning
confidence: 95%
“…44 A recent study showed no association with anxiety, depression, or cognitive dysfunction. 25 Nonetheless, it is still reasonable to have a low threshold for therapy for SCH in patients with depression, bipolar disorder, and cognitive dysfunction.…”
Section: Psychiatric and Cognitive Dysfunctionmentioning
confidence: 95%
“…Subclinical or mild hypothyroidism is common in women and in the elderly and has been associated with alteration in the lipoprotein profile, such as increased cholesterol, and with increased incidence of depression by lowering of the threshold for the development of major depressive disorders (40) and other mood disorders (41,42). In addition, mild hypothyroidism has been linked with diminished response to standard psychiatric treatment and with cognitive dysfunction (41). A 0.26 ng/dL geometric mean difference in free T4 in women during the second trimester of pregnancy has been associated with an average 4-point IQ reduction in their children (0.97 ng/dL vs. 0.72 ng/dL; p < 0.001) (43).…”
Section: Borderline Hypo-and Hyperthyroidismmentioning
confidence: 99%
“…In adults, these states are reversible and psychological testing of hypothyroid patients has consistently revealed that intellectual impairment subsides with thyroxine treatment (2,3).…”
Section: Introductionmentioning
confidence: 99%